To what extent the World Health Organization's policies of antimicrobial resistance are implemented in Egyptian hospitals. - Hussein, Amira Farouk (AUC Knowledge Fountain, 2019)
Antimicrobial resistance is a major public health problem. In the Egyptian hospitals, the problem was discovered since 2006; however, seven years ago, this problem drew the attention to be one of the major risk factors worldwide and in the Egyptian hospitals as well. International organizations, such as the World Health Organization (WHO) tried to find different solutions to prevent transmission of these communicable diseases from country to another by setting different guidelines and standards to be followed by countries. The case is to assess the barriers to implementation of objectives and guidelines of WHO in one of the biggest public Egyptian hospitals, in order to have enough knowledge and gather information about the current situation in Egypt. In order to fulfill these objectives, a case study from a large public hospital was extensively studied through qualitative research methods including interviews and observational studies. Findings of the current research are most relevant to public hospitals which serve a huge sector in developing countries. Behavioral factors such as weak managerial support, lack of communication between healthcare departments, absent standards and guidelines for diagnosis and treatment, and subjective decisions in managing patients' cases are among the major factors contributing to the problem. Nonbehavioral factors such as inadequate infrastructure and poor resources are also existing. The results give a substantial contribution in identifying the behavioral causes of the prevalence of multidrug resistance (MDR) problem in Egypt and shed light on the possible solutions.